2015
DOI: 10.1371/journal.pone.0123604
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Immediate Early Gene Protein Expression in the Spinal Cord following Conditioning Stimulation of the Sciatic Nerve in Rats

Abstract: Long-term potentiation induced by conditioning electrical stimulation of afferent fibers is a widely studied form of synaptic plasticity in the brain and the spinal cord. In the spinal cord dorsal horn, long-term potentiation is induced by a series of high-frequency trains applied to primary afferent fibers. Conditioning stimulation (CS) of sciatic nerve primary afferent fibers also induces expression of immediate early gene proteins in the lumbar spinal cord. However, the time course of immediate early gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…EGR1 induction is detectable within ∼30 to 60 min following a noxious stimulation. 12 , 13 The histologic visualization of a fluorescent conjugate of AYX1 in the lumbar spinal cord and DRG 30 min following an IT injection shows that AYX1 is already present in cell nuclei ( Figure 4 ), where it can compete with the newly induced EGR1. EGR1 induction is known to continue for at least 720 min following the initial stimulation, as illustrated in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EGR1 induction is detectable within ∼30 to 60 min following a noxious stimulation. 12 , 13 The histologic visualization of a fluorescent conjugate of AYX1 in the lumbar spinal cord and DRG 30 min following an IT injection shows that AYX1 is already present in cell nuclei ( Figure 4 ), where it can compete with the newly induced EGR1. EGR1 induction is known to continue for at least 720 min following the initial stimulation, as illustrated in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies in the spinal cord have shown that EGR1 induction is detectable from 30 to 60 min up to at least ∼12 h following a noxious or sensitizing stimulus. 12 , 13 The pharmacokinetic properties of single strand oligonucleotides are just beginning to be understood 14 17 and to the best of our knowledge, no information is publicly available regarding IT injection of DNA-decoys as a class of molecules. We characterized AYX1 local pharmacokinetics (PK) and metabolism features driving AYX1 exposure in the lumbar cerebrospinal fluid (LCSF), DRG, and spinal cord during that timeframe.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of the activity of dorsal horn neurons is a key outcome/endpoint following activation of the descending pain pathway (Bojovic et al, 2015;Gao and Ji, 2009). The fact that the behavioural effects of the drugs administered are not accompanied by drug-induced effects on c-Fos expression in the dorsal horn may suggest that the behavioural effects of pharmacological manipulation of TRPV1 in the DLPAG are not mediated by modulation of the descending pain pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among the transcripts with significant increases in translation was the immediate early gene Arc ( Figure 1G). While Arc is expressed in the spinal cord, it is unclear if it is present in DRG neurons (Bojovic et al, 2015;Hossaini et al, 2010;Minatohara et al, 2015;Plath et al, 2006). To validate if Arc is translated in response to inflammatory mediators, we conducted immunoblots on cultured DRG exposed to NG/IL-6 ( Figure 1H).…”
Section: Introductionmentioning
confidence: 99%